A review of food advertisements and childhood obesity and an exploration of the impact of food policies - Hakeem, Sarah (My University, 2013)
Objective: The purpose of this study was to review food television advertisement policies that currently exist in multiple countries and to review the published literature on children's television viewing behaviors, the relationship of children's television viewing and childhood obesity, and the relationship of food television advertisements directed toward children and childhood obesity. Three research questions investigated in this current study follow: 1. What policies exist for marketing food products through television advertisements directed toward children? 2. Who is responsible for children watching food advertisements? 3. Are food television advertisements different between multiple countries? Methods: The EBSCOhost database platform was accessed in order to search multiple databases with multiple layers of search terms. Professional and academic articles were selected for review using predefined inclusion and exclusion criteria. Results: Many factors affect children's decision making as a result of television advertisements. Some factors that are found to influence their choices include the use of toys, repeat advertisements, advertisement duration, environment, and parental education. Current policy states that rules do not only come from government. Parents are also responsible for creating rules to restrict television watching at home. The role of government is to restrict the length of advertisements while also monitoring the types of food that is advertised. Conclusions: Most research recommends strict parental guidance of children and adolescents. Schools are also responsible for helping children make healthy food choices. Government, on the other hand, is responsible for limiting the number of television advertisements shown.
This file was last viewed in Adobe Reader X.
Keywords: Television advertising and children; Advertising--Food; Obesity in children; Food industry and trade--Government policy